(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es ((3EHQGgje GdbaWGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdLgGO ef GdLgO HGdaJM dZI GdeTbI Ch efg HGdVe CjkVG GdhSY hGdWGbI hTQYG HPd GdfaS heG jJhba Ydjg ef GdeGd aj eMGQHI GdeTQcjfs
(3BNQgG (B:s
(3BNQgG(B: (3bGd Ydj Hf GdMSjf(B: (3EPG cfJe aj CFeI LhQ aGeVhG aj CMcGege hdG JTgQhG CfaSce aJbJdhG hGdYGde gh HMbGFb CMcGegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis